Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-344
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Belts and Whistles: A Preliminary Study of Breathing Acoustics for Turn-Taking

Abstract: This paper presents first results on using acoustic intensity of inhalations as a cue to speech initiation in spontaneous multiparty conversations. We demonstrate that inhalation intensity significantly differentiates between cycles coinciding with no speech activity, shorter (< 1 s) and longer stretches of speech. While the model fit is relatively weak, it is comparable to the fit of a model using kinematic features collected with Respiratory Inductance Plethysmography. We also show that incorporating both ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The study was based on the same material used in [10]. The description of the recording setup and data pre-processing is repeated below for completeness.…”
Section: Methodsmentioning
confidence: 99%
“…The study was based on the same material used in [10]. The description of the recording setup and data pre-processing is repeated below for completeness.…”
Section: Methodsmentioning
confidence: 99%
“…RST is used in the diagnosis of the sleepless syndrome, and its purpose is to know if the upper body is inflamed by examining the signals of a patient's respiration. The two RST have been used previously in examining the differences in speech rhythm ( [7], [8]), the correlation between pitch and intensity ( [9]), gender differences ( [10]), the F0 declination ( [11]), and turn-taking in dialogue ( [12]), among other uses.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the works that consider respiration, data is captured with respiration sensors such as belt-like strips placed on the chest (e.g., [26,58]), or with other dedicated devices. An example of such a device is the CO2100C module by Biopac 1 that measures the quantity of C O 2 in the exhaled air.…”
Section: Methods For Measuring the Respirationmentioning
confidence: 99%
“…Wlodarczak and Heldner [58] studied the communicative functions of respiratory sounds. They found that acoustic intensity of inhalation is the feature that allows one to detect the forthcoming turn-takings.…”
Section: Measuring Respiration From the Audio Signalmentioning
confidence: 99%